1991
DOI: 10.1122/1.550257
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of extremely shear thickening polymer dispersionsa) (passively viscosity switching fluids)

Abstract: SynopsisThe flow properties of concentrated polymer dispersions which exhibit extreme shear thickening have been investigated in steady and transient shearing flows using various types of rheometers. A phenomenological characterization based on few fluid parameters is proposed and pertinent test modes for their determination are discussed. The dispersions consist of monodisperse, electrostatically stabilized, solid spherical particles (diameter <0.5 /Lm) dispersed in glycols. They show a reversible steplike vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(106 citation statements)
references
References 20 publications
(27 reference statements)
3
102
1
Order By: Relevance
“…Finally we can compare our results with those obtained by Laun (20). He also found Journal qfCotloid and Interface Science, Vol.…”
Section: R = 2a(074/4) 1/3 the + And -Signs Insupporting
confidence: 49%
See 1 more Smart Citation
“…Finally we can compare our results with those obtained by Laun (20). He also found Journal qfCotloid and Interface Science, Vol.…”
Section: R = 2a(074/4) 1/3 the + And -Signs Insupporting
confidence: 49%
“…Most of his work was concerned with the steady shear or linear viscoelastic properties. In his most recent paper (20), however, he also deals with the nonlinear viscoelastic properties of concentrated shearthickening dispersions.…”
Section: -9797/92 $300mentioning
confidence: 99%
“…In the present model, such an aspect of hardening is represented by the fact that the relaxational time scale for the state change is not constant but proportional to the shear rate (7). Then, the state variable φ reaches a steady value φ * in a time scale where the strain changes by the amount r. Consequently, the medium with φ M 1 can deform only up to a certain strain around r by a hard impact.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…There are several peculiar features in the shear thickening of the dilatant fluid: (i) the thickening is so severe and instantaneous that it might be used even to make a body armor to stop a bullet [6], (ii) the relaxation after removal of the external stress occurs within a few seconds, that is quick but not as instantaneous as in the thickening process, (iii) the medium in the thickened state behaves like a rigid material allowing little elastic deformation as long as it is under stress, (iv) the viscosity shows hysteresis upon changing the shear rate [7], (v) noisy fluctuations have been observed in the response to an external shear stress in the thickening regime [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Fischer et al [24] demonstrated the potential for integrating STFs into structures exposed to dynamic flexural deformation by controlling their vibrational response. Laun et al [25] and Helber et al [26] investigated the damping behavior of STFs and suggested they could be used in damping and mounting of industrial machinery. STFs have also been studied in the applications of smart structures.…”
mentioning
confidence: 99%